Revolutionary Rites: Political Demonstrations at the Place de la Nation, Paris - Germani, Ian (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2011)
Historians who study sites of memory emphasize the fluidity in meaning attached to those sites. The meaning of monuments is dependent upon changes in political context, which affect both how they are perceived and the uses to which they are put. With specific attention to the Place de la Nation in Paris and to Dalou’s monument, Le Triomphe de la République, this article argues that street demonstrations have played an important role in creating meaning for Parisian sites of memory. It focuses on four events in the history of the Place/monument: the inauguration of the bronze statue on 19 November, 1899; the demonstration marking the formation of the Popular Front on 12 February, 1934; the “bloody” 14 July demonstration of 1953; and the demonstration against Jean-Marie Le Pen and the National Front on 1 May, 2002. While the specific political context of these demonstrations varied, as did the character and purpose of the actors composing them, they all provided an occasion for the rehearsal of France’s revolutionary traditions, with particular reference to the Paris Commune. The transitory nature and specific purposes of particular demonstrations, however, restricted their ability to alter the monument’s significance. This is painfully apparent in the case of the Algerian demonstration of 14 July, 1953, which ended in a quickly forgotten massacre.